Sectoral GDP Convergence of Selected RCEP Countries: Lead or Lags? - Dyg Affizzah, Awang Marikan; Md Mahbubur, Rahman; Nor Afiza, Abu Bakar; Mohammad Affendy, Arip (UNIMAS Publisher, 2017)
The study investigates sectoral value added convergence in selected RCEP countries by applying the non-linear time-varying coefficients factor model suggested by Phillips and Sul (2007a) over the period of 1987-2015. Structural convergence occurs, if income convergence progress is associated with sectoral convergence or disaggregated level. Interestingly, this investigation finds income converge at the aggregate level. To investigate further, further clustering algorithm is applied and resulted in three clubs, indicating advanced countries (Japan, Singapore and Korea) lead club, Upper-middle income countries (Malaysia, China and Thailand) as second club,and finally lower middle income (Indonesia, Philippines and India) form another club. The three sector hypothesis states that, inter sectoral convergence is anticipated to appear whenever the less developed nations are capable of closing the income disparity with those advanced nations as Asian in this study. Convergence in Income per capita was quite rapid, indicating the highest level of convergence at sectoral level. For robustness, this application offered the measures of value added convergence in five sectors namely, agriculture, manufacture, service, construction and mining sectors. The study shows an obvious indication for Asian catching up countries to form large clusters that shall be useful in policy formulation for further integration of RCEP.